Chemical composition, bactericidal, and antioxidant activity of the essential oils in the leaves of Ocimum basilicum and Ocimum gratissimum (Lamiaceae) (Research, Society and Development, 2021)
The Ocimum genus of the Lamiaceae family comprises a group of well-known plants such as Ocimum gratissimum L. (lavender) and Ocimum basilicum (basil). Studies reveal that plants have antimicrobial, insecticidal, antioxidant, antifungal, analgesic and immunostimulant activity. Thus, the objective of this study was to analyze the chemical composition of the essential oils of O. gratissimum and O. basilicum collected at different times and with different extraction times, as well as to evaluate their antioxidant activity, total phenolic content and activity bactericide on Staphylococcus aureus and Escherichia coli. The essential oil was obtained by hydrodistillation in a Clevenger type apparatus, and the chemical composition was carried out in a gas chromatograph coupled to the mass spectrometer (GC-MS); the analysis of antioxidant activity was performed in 96-well microplates with the addition of 2,2-diphenyl-1-picrylhydrazyl (DDPH) in methanol; the total phenolic content was carried out in 96-well microplates using Folin-Ciocalteu to determine the gallic acid content; and the bactericidal activity performed by the method of diffusion of discs in the Petri dish and method of diffusion in Muller-Hinton broth in 96-well plates. The highest yield of the essential oil of O. gratissimum was 0.44% when collected in the morning, while the essential oil of O. basilicum had a yield of 0.38% when collected in the afternoon, both with four hours of extraction. The major compounds of O. gratissimum were eugenol and eucalyptol, while the major compounds of the essential oil of O. basilicum were eugenol, β-linalool and muurolol. The antioxidant activity was 100% free radical scavenging DPPH in the highest concentrations of essential oil 15.6 µg mL-1 for both, O. gratissimum and O. basilicum. The total phenolic compounds content of the essential oils of O. gratissimum and O. basilicum was 17.90 and 16.44 mg AGE 100 g-1 respectively. The essential oils of O. gratissimum and O. basilicum presented 100% and 83% of bactericidal activity against Staphylococcus aureus, and the 100% to 66% on Escherichia coli, respectively, thus highlighting the biotechnological potential of these essential oils.